2012
DOI: 10.1007/978-3-642-27645-3_17
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning in Games

Abstract: Abstract. Reinforcement learning and games have a long and mutually beneficial common history. From one side, games are rich and challenging domains for testing reinforcement learning algorithms. From the other side, in several games the best computer players use reinforcement learning. The chapter begins with a selection of games and notable reinforcement learning implementations. Without any modifications, the basic reinforcement learning algorithms are rarely sufficient for high-level gameplay, so it is ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 68 publications
0
25
0
1
Order By: Relevance
“…The second is partially observable and extends the partially observable Markov decision process (POMDP) (Cassandra, 1998; Kaelbling et al, 1998;. The single-objective version of these models are widely used and applied in areas such as: communication networks (Altman, 2002), planning and scheduling (Scharpff et al, 2013), games (Szita, 2012) and robotics (Kober and Peters, 2012). The multi-objective models have been gaining traction relatively recently.…”
Section: Sequential Decision-makingmentioning
confidence: 99%
“…The second is partially observable and extends the partially observable Markov decision process (POMDP) (Cassandra, 1998; Kaelbling et al, 1998;. The single-objective version of these models are widely used and applied in areas such as: communication networks (Altman, 2002), planning and scheduling (Scharpff et al, 2013), games (Szita, 2012) and robotics (Kober and Peters, 2012). The multi-objective models have been gaining traction relatively recently.…”
Section: Sequential Decision-makingmentioning
confidence: 99%
“…There is partial evidence for many factors being involved here; Szita [16] suggested that policy representation (relying on function approximation), the presence of randomness, environment observability, and training regime are, among others, the critical factors. In this study, we focus on policy representation and, more specifically, on its dimensionality, meant as the number of variables/parameters that characterize candidate policies.…”
Section: Introductionmentioning
confidence: 97%
“…the actions to take in the MDP states in order to maximise the obtained rewards (Wiering and Otterlo, 2012). Although successfully used in applications ranging from gaming (Szita, 2012) to robotics (Kober et al, 2013), standard RL is not applicable to problems where the policies synthesised by the agent must satisfy strict constraints associated with the safety, reliability, performance and other critical aspects of the problem.…”
Section: Introductionmentioning
confidence: 99%